Fishery and population dynamics of Caspian kutum, Rutilus frisii kutum (cyprinidae), in the Caspian Sea - Bandpei, Mohammadali Afraei (2010)
The Caspian Sea is the largest enclosed body of water in the world. The water is slightly brackish. The aim of project was to determine length at maturity (Lm50%), evaluate of feeding items, investigation some of biological aspects included in sex ratio, growth and age structure, instantaneous mortality coefficient, maximum sustainable yield (MSY) and break-even point of Rutilus frisii kutum in southern part of the Caspian Sea. Specimens of Kutum were collected from the catches obtained from 131 sample sites along the Iranian coast of the Caspian Sea.